Beirut the eras of design - Costantini, Marco 1970- (Kaph, 2022)
The first overview of Lebanon's thriving design scene from the 1920s to the present, with works by more than 50 designers. The vibrancy of Lebanese design stands out as exceptional in the region and should be understood via the country's long-standing cultural relations with Europe (especially France)--but also with the Emirates and their ancient craft traditions. This publication analyzes Lebanese design's unique convergence of economic and architectural reconstruction, social awareness and international development. It also testifies to the designers' determination to take ownership of their destiny and image by presenting objects and forms that are simultaneously aware of their diverse heritage and are deeply rooted in a complex reality.
Catalogue of an exhibition held at CID, Centre d'innovation et de design, au Grand-Hornu, Belgium, April 24-August 14, 2022, and 'mudac', Musée de design et d'arts appliqués contemporain, Lausanne, Switzerland, March 15-July 25, 2023
Exhibition organized by mudac, Lausanne and co-produced with CID, Grand-Hornu
Translated from French to English: Laura Bennett, Susan Mackervoy, Trista Selous
Keywords: Interior decoration / Exhibitions; Interior decoration / Lebanon / Beirut / Exhibitions; Interior decoration; Lebanon / Beirut; Exhibition catalogs; Ausstellungskatalog -- Centre d'innovation et de design -- 24.04.2022-14.08.2022 -- Hornu; Ausstellungskatalog -- mudac - Musée de design et d'arts appliqués contemporains -- 15.03.2023-25.07.2023 -- Lausanne